Assessment of Satisfaction Levels Among Families of Intensive Care Unit Patients in Saudi Arabia: A Cross-Sectional Study - Abdullah Shbeer; Mohammed Ageel (Critical Care Research and Practice)
Conclusions: This study revealed moderate to high levels of family satisfaction with the ICU, with significant differences based on sex. The findings highlight the importance of effective communication, family involvement in decision-making, and supportive ICU policies. ICUs should regularly assess family satisfaction and use the results to guide quality improvement efforts, with a focus on areas with lower satisfaction scores.